2011
DOI: 10.4028/www.scientific.net/amr.396-398.2052
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Enzymatic Extraction Treatment on Physicochemical Properties, Microstructure and Nutrient Composition of Tartary Buckwheat Bran: A New Source of Antioxidant Dietary Fiber

Abstract: The effect of enzymatic treatment with amylase and cellulase on Tartary Buckwheat (F. tataricum Gaertn) bran dietary fiber was evaluated by studying its chemical composition, physicochemical property and microstructure. Tartary buckwheat bran flour, obtained from residues of tartary buckwheat processing exhibited high contents of dietary fiber (44.2±0.3%), starch (31.94±0.27%), lipid (5.18±0.14%) and total ash (2.91±0.04%), and a low level of crude protein (3.12±0.11%). The contents of hemicellulose, cellulose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…Among all treatments, the highest results were shown by cooking without soaking. Therefore, it was concluded that thermal processes can also change the ratio of soluble and insoluble fibers and physicochemical properties of dietary fiber (Zhou et al, ). These modify the composition and availability of nutrients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among all treatments, the highest results were shown by cooking without soaking. Therefore, it was concluded that thermal processes can also change the ratio of soluble and insoluble fibers and physicochemical properties of dietary fiber (Zhou et al, ). These modify the composition and availability of nutrients.…”
Section: Resultsmentioning
confidence: 99%
“…For the purpose, thermal processes are considered as most important approach for the modification of soluble and insoluble fibers ratio and physicochemical properties of dietary fiber (Zhou, Qian, Zhou, & Zhang, ). Different methods are used for thermal modification such as sterilization, sun drying, steam processing, boiling, frying mainly deep fat frying, microwave drying, vacuum‐belt drying, roasting, and pressure cooking.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al (2012) reported that the water-holding capacity and swelling capacity of Tartary buckwheat (Fagopyrum tataricum Gaertn.) bran dietary fi ber were improved after enzymatic treatment, due to the increase in SDF/IDF and the decreased size of dietary fi ber particles.…”
Section: Enzymatic Processesmentioning
confidence: 99%
“…3(a) shows that the WHC of O-IDF and M-IDF was 7.10 g/g and 16.15 g/g, respectively. Both O-IDF and M-IDF also exhibited higher WHC values than the wheat IDF reference ( p < 0.05) and agricultural by-products from other fibers, e.g., 2.58 g/g from tartary buckwheat bran fiber (Zhou, Qian, Zhou, & Zhang, 2011), 3.6 g/g from rice bran DF (Wen et al, 2017), 6.1 g/g from wheat bran, 2.32 g/g from maize hulls, 2.48 g/g from wheat hulls and 4.9 g/g from soybean fiber (Alfredo, Gabriel, Luis, & David, 2009). The increase in the WHC of M-IDF according to the increase in the hydrogen peroxide process might be mainly attributable to the destruction of lignocellulose biomass structure.…”
Section: Resultsmentioning
confidence: 95%